Digital Leadership and Digital Transformation in School Management: Implications for Learning Quality Enhancement with Organizational Culture as Moderator - Halim, Didin; Salam, Rudi; Purna, Zarni Adia (Universitas Negeri Makassar, 2025)
Digitalization in education has become an urgent necessity in accordance with technological advancement and evolving demands in learning systems. This study aims to analyze the influence of digital leadership and digital transformation on learning quality enhancement with organizational culture as a moderating variable. The research employs a quantitative method with an explanatory design involving 120 respondents from senior high schools in Maros Regency. Data were collected through Likert-scale questionnaires and analyzed using Structural Equation Modeling (SEM) Partial Least Squares (PLS) with SmartPLS 4.0 software. The findings demonstrate that digital leadership exerts a positive and significant influence on learning quality (β=0.345, p<0.001) and digital innovation (β=0.622, p<0.001). Digital innovation also exhibits a robust effect on learning quality (β=0.587, p<0.001) and is proven to be a significant partial mediator (β=0.365, p<0.001) in the relationship between digital leadership and learning quality. The research model demonstrates excellent fit with a Goodness of Fit (GoF) value of 0.676 and explains 68.8% of the variance in learning quality (R²=0.688). The findings confirm that the amalgamation of effective digital leadership with digital innovation culture generates more optimal transformation in enhancing learning quality. This research provides practical contributions to the development of digital leadership strategies and sustainable implementation of digital transformation in educational institutions.